Effects of stride length and running mileage on a probabilistic stress fracture model - Edwards, W. B.; Taylor, D.; Rudolphi, T. J.; Gilette, J. C.; Derrick, T. R. (Medicine & Science in Sports & Exercise, 2009)
ABSTRACT: The fatigue life of bone is inversely related to strain magnitude. Decreasing stride length is a potential mechanism of strain reduction during running. If stride length is decreased, the number of loading cycles will increase for a given mileage. It is unclear if increased loading cycles are detrimental to skeletal health despite reductions in strain.